Dendrite-free Li metal plating/stripping onto three-dimensional vertical-graphene@carbon-cloth host - Yan, Congcong (2020)
Lithium metal is deemed as an ideal anode material for next-generation lithium ion batteries (LIBs) due to its high specific capacity and low redox potential. However, uncontrolled lithium dendrite formation during electrochemical deposition leads to a low Coulombic efficiency and serious safety issues, dragging metallic lithium anodes out of practical application. One promising strategy to suppress lithium dendrite issues is employing a three-dimensional host with admirable conductivity and large surface area. Herein, a vertical graphene nanosheet grown on carbon cloth (VG/CC) synthesized is adopted as the Li deposition host. The three-dimensional VG/CC with a large surface area can provide abundant active nucleation sites and effectively reduce the current density, leading to homogeneous Li deposition to overcome the dendrite issue. The Li@VG/CC anode exhibits a dendrite-free morphology after a long cycle and superior electrochemical performance to that of planar Cu current collector. It delivers a small voltage hysteresis of 90.9 mV at a high current density of 10 mA cm-2 and a Coulombic efficiency of 99% over 100 cycles at 2 mA cm-2. Our results indicate that this all-carbon-based nanostructure host has great potential for next-generation Li metal batteries.